FORMULASI SEDIAAN SPRAY GEL EKSTRAK ETANOL KULIT BUAH MANGGIS (GARCINIA MANGOSTANA L.) SEBAGAI HAND SANITIZER TERHADAP BAKTERI STAPHYLOCOCCUS AUREUS - Wulan Ratia Ratulangi, Wulan Ratia Ratulangi (Pharmaceutical and Traditional Medicine, 2022)
Hand sanitizer is in the form of a spray gel with various ingredients that quickly kill microorganisms on the skin. hand sanitizer is widely used for practical reasons, easy to carry everywhere and can be used quickly without using water. mangosteen rind (garcinia mangostana l.) contains various secondary metabolites which exhibit certain biological activities, namely antioxidants. the purpose of this study was to determine whether the formulation of spray gel hand sanitizer ethanol extract of mangosteen rind had antibacterial activity against staphylococcus aerius and to find out what concentration of the formulation of spray gel hand sanitizer ethanol extract of mangosteen rind was the most effective antibacterial against staphylococus arius. the method used in this study is the remeseration method using 96% solvent. the dosage formulation was made using hpmc as a gelling agent. spray gel hand sanitizer ethanol extract of mangosteen rind was made in 3 formulations. formulation 1 contains 10% mangosteen rind extract, formulation 2 contains 20% mangosteen rind extract, mangosteen rind extract. negative control is a formulation of spray gel hand sanitizer without extract and negative control uses spray gel hand sanitizer brand x with the active substance of alcohol as an antibacterial agent. the data obtained were organoleptic test, ph test, homogeneity test spreadability test, and antibacterial activity test. formula 1 ph value was in accordance with the ph of the skin, had good dispersion, and the homogeneity test showed that there were no coarse grains contained in the four formulations. the results of the antibacterial test showed that the mangosteen rind extract was applied as a hand sanitizer spray gel at concentrations of 10%, 20%, and 30%. can inhibit or the most optimum bacterial growth inhibiting bacteria is at a concentration of 30% extract which produces an inhibitory zone of 9.08 mm in staphylococcus aureus.